Nitrogen-doped MXene / TiO2 composite flexible electrode material and preparation method and application thereof
By removing the A atomic layer in the MXene material and performing intercalation treatment and solvothermal reaction, a nitrogen-doped MXene/TiO2 material with high nitrogen content was prepared, which solved the self-stacking and structural instability of the MXene material, and realized the High conductivity and excellent electrochemical properties simplify the process and improve specific capacitance.
Patent Information
- Application Number
- CN202310849636.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-11
- Publication Date
- 2025-01-14
AI Technical Summary
In the prior art, MXene materials have self-stacking problems and structural instability in electrochemical energy storage applications, and the existing nitrogen doping methods are complex in operation, poor in effect, or lead to performance degradation.
After removing the A-atom layer of the MAX-phase ceramic material, the nitrogen-doped MXene/TiO2 material with high nitrogen content was prepared by using a compound that ionizes ammonium ions and undergoes solvothermal reaction with the nitrogen-containing compound. , simplifies the process and generates spacer TiO2 in situ, alleviating the stacking effect.
The high conductivity and excellent electrochemical properties of MXene materials are achieved, the specific capacitance is improved, the preparation process is simplified, and the flexibility and efficiency of the material are maintained.
Smart Images

Figure CN119314805A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation and relates to a nitrogen-doped MXene / TiO2 composite material for preparing a flexible electrode and a preparation method thereof. Background Art
[0002] In 2011, Gogotsi et al. first used hydrofluoric acid to selectively remove aluminum from titanium-aluminum carbide (Ti3AlC2) powder at room temperature to obtain two-dimensional (2D) layered carbide material Ti3C2 nanosheets. Later, this type of new 2D transition metal carbide, nitride or carbonitride layered material with a thickness of a few atoms was collectively referred to as MXene. Mashtalir et al. obtained a single-layer MXene sheet by inserting organic molecules such as dimethyl sulfoxide and performing ultrasonic layering treatment, officially opening a new era of 2D material MXene research. Unlike most 2D materials, MXene not only has the common properties of 2D materials, but also has better characteristics: (1) Due to the diversity of M elements, MXene can have rich chemical compositions; (2) Through different preparation methods, the surface terminal groups of MXene can be adjusted; (3) The large separation of orbital energy levels between M and X atoms and the effective use of surface terminal groups make MXene reach or even exceed the metallic conductivity of crystallized graphene; (4) The hydrogen bonds between water molecules and the ends make MXene hydrophilic, etc. Due to its versatile chemical properties and rich surface modification space, MXene has played an important role in various technical applications such as energy storage, catalysis, sensors, electromagnetic interference shielding and lubrication. Among them, MXene has attracted more and more attention due to its special advantages as an electrode material in electrochemical energy storage devices, but MXene itself also has some disadvantages, such as (1) the interlayer van der Waals force makes MXene prone to serious self-stacking problems and (2) the metal atoms exposed on the surface of MXene are easily oxidized and cause structural damage. These defects limit its application in energy storage, and the development of more advanced MXene electrode materials is crucial for the next generation of high-performance electrochemical energy storage devices.
[0003] The performance of MXene in the field of energy-related devices has attracted much attention, and surface / structural modification of MXene is one of the important ways to improve its performance. Heteroatom doping of graphene can effectively adjust its electronic structure and intrinsic properties, thereby improving its electrochemical performance. In particular, nitrogen-doped graphene performs well in capacitance and rate performance. Inspired by this, N-doping of MXene layers is an effective means to improve their conductivity and redox activity. In addition, the wrinkle formation and increased electrostatic repulsion after N-doping MXene can alleviate the stacking effect of MXene and promote the penetration of electrolytes between layers, thereby improving its electrochemical performance.
[0004] The introduction of "spacers" can effectively alleviate the stacking problem of MXene. Low-dimensional inorganic nanostructures are usually introduced to disperse between adjacent MXene layers to isolate their self-stacking, thereby protecting the electroactive sites from being sacrificed. However, since these inorganic nanoparticles tend to aggregate during the hybridization process, it is difficult to ensure that the implanted nanoparticles can be evenly loaded between MXenes, increasing the instability of the structure. In addition, the weak intrinsic interaction between MXenes and particles may lead to the loss of the good conductivity of MXene itself.
[0005] At present, the preparation methods of MXene in the direction of heteroatom doping include plasma treatment, microwave irradiation gas phase method and heat treatment method. However, the operation of plasma treatment method is complicated and will destroy the structure of the material itself; the doping effect of microwave irradiation gas phase method is not good and cannot be prepared on a large scale; the heat treatment method causes the deterioration of MXene structure and performance degradation due to high temperature annealing. Therefore, it is necessary to find a new green, safe, simple and low stacking effect nitrogen-doped MXene preparation method. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide an N-doped MXene / TiO2 material with excellent electrochemical properties and ultra-high specific capacitance, as well as a preparation method and application thereof, in view of the above-mentioned deficiencies in the prior art.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0008] Provided is an N-doped MXene / TiO2 material. First, a MAX phase ceramic material is etched to remove the A atomic layer, and then washed and dried to obtain a multilayer MXene material. The multilayer MXene is then intercalated and layered with a compound that can ionize ammonium ions. Finally, a nitrogen-containing compound is used as a nitrogen source to perform a solvent thermal reaction with a single-layer MXene. The product after the reaction is washed and dried to obtain a high-nitrogen-content nitrogen-doped MXene / TiO2 material.
[0009] According to the above scheme, the MAX phase ceramic material is of M2AX type or M3AX2 type, wherein M is a transition metal element, A is a main group element or a rare earth element, X is carbon or nitrogen, and the particle size is 400 mesh.
[0010] According to the above scheme, the mixing ratio of the multilayer MXene and the compound capable of ionizing ammonium ions is 1 g: 1 to 10 mol per liter of the mixed solution.
[0011] According to the above scheme, the mass ratio of the single-layer or few-layer MXene to the nitrogen source is 1 / 10 to 1 / 50.
[0012] According to the above scheme, the solvent thermal process conditions are: 120°C to 250°C, and keep warm for 5 to 20 hours.
[0013] The present invention also provides a method for preparing the above-mentioned N-doped MXene material, and the specific steps are as follows:
[0014] 1) Immerse the MAX phase ceramic material in lithium fluoride and 9M hydrochloric acid solution, stir at 30-45°C for 24-72h to etch away the A atomic layer in the MAX phase ceramic material, then wash and centrifuge until the pH value of the washing liquid is greater than 6 to obtain a multilayer MXene phase material, then place the multilayer MXene phase material in a compound that can ionize ammonium ions at room temperature for stirring intercalation treatment, then centrifuge under aqueous medium conditions, and finally ultrasonically peel and vacuum dry to obtain a single-layer or few-layer MXene phase material;
[0015] 2) The multilayer MXene phase material obtained in step 1) is added to 0.5-1M ammonium salt, and the ammonium ion compound is ammonium citrate, thioacetamide, urea, glycine, etc., and stirred for intercalation treatment, followed by washing and centrifugation, and finally ultrasonic stripping and vacuum drying to obtain NH4 + Processed single-layer or few-layer MXene phase materials;
[0016] 3) NH4 obtained in step 2) + The treated single-layer or few-layer MXene phase material and the nitrogen source are added to a high-pressure reactor in a certain proportion, and the solvent thermal reaction is carried out for a certain period of time. After the reaction, the powder is washed and dried to obtain a high-nitrogen-content nitrogen-doped MXene / TiO2 material.
[0017] Preferably, in the step 3), the reaction mass ratio of the few-layer MXene material to the nitrogen source is 1:10-50; and the nitrogen source is a nitrogen-containing compound, at least one of ammonium bicarbonate, ammonia water, urea, ammonium chloride, ammonium carbonate, ammonium acetate, ammonium sulfate, ammonium oxalate, and ammonium acetate.
[0018] Preferably, in step 2), the solvent heat treatment process conditions are: 120° C. to 250° C., and insulation time is 5 to 20 hours.
[0019] The present invention also includes the use of the above-mentioned N-doped MXene material in a supercapacitor.
[0020] The present invention also includes the application of the above-mentioned N-doped MXene material in energy storage fields such as supercapacitors and lithium-ion batteries.
[0021] The beneficial effects of the present invention are as follows: 1. The N-doped MXene / TiO2 material prepared by the present invention has a single-layer flaky structure, which is beneficial to the transmission rate of electrolyte ions and improves the electrochemical performance of the electrode material. In addition, since the N-doped MXene material has a higher conductivity, a larger interlayer spacing, and exposes more active sites, the pseudocapacitance and conductivity of the MXene itself are improved. Compared with the MXene material, the N-doped MXene / TiO2 material has a more excellent electrochemical performance and an ultra-high specific capacitance; 2. The preparation method of the N-doped MXene / TiO2 material provided by the present invention is simple to operate, and the NH4 + After intercalation and layering pretreatment, a simple solvothermal reaction is performed to N-dope MXene and simultaneously generate "spacer" TiO2 in situ, which greatly simplifies the N-doping process, increases the content of doped N, effectively alleviates the stacking effect of MXene, maintains the flexibility of MXene materials, and enhances the specific capacitance of MXene materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0023] Figure 1 This is a digital photo of the nitrogen-doped MXene / TiO2 material prepared in Example 1 of the present invention;
[0024] Figure 2 This is a flexible thin film electrode obtained by filtration of the nitrogen-doped MXene / TiO2 material prepared in Example 1 of the present invention.
[0025] Figure 3 The electrochemical properties of the flexible thin film electrode (N-MXene / TiO2) obtained by filtration of the nitrogen-doped MXene / TiO2 material prepared in Example 1 of the present invention are compared with those of the original MXene thin film electrode. DETAILED DESCRIPTION
[0026] In order to better understand the present invention, the present invention is further specifically described below through the following examples, but it should not be understood as limiting the present invention. For those skilled in the art, some non-essential improvements and adjustments made according to the above invention content should also be considered to fall within the protection scope of the present invention. Next, the technical solution of the present invention will be further described in conjunction with specific embodiments.
[0027] [Example 1]
[0028] This embodiment provides a method for preparing nitrogen-doped Ti3C2T3 with high nitrogen content. x The method of MXene / TiO2 material, the specific steps are as follows:
[0029] 3.2 g of lithium fluoride was dissolved in HCl (9 M, 30 mL) in a polytetrafluoroethylene beaker. Ti3AlC2 MAX phase powder (2 g) was slowly added. The mixture was heated to 40 ° C and stirred in a sealed beaker for 48 h. The mixture was then diluted 50 times with water and centrifuged at 3500 rpm for 1 min. The centrifugal washing was repeated at least 5 times until the supernatant reached a pH of more than 6. The aqueous dispersion obtained at this stage contained multilayer MXene nanosheets, which were frozen in liquid nitrogen and dried in a freeze dryer for 48 h. Multilayer MXene powder was obtained.
[0030] Multilayer Ti3C2T x The MXene material was washed with deionized water to a pH of 7, then washed with ethanol and dried in vacuum. x The MXene material was added to 0.5-1 M ammonium citrate and stirred thoroughly for 4 h for intercalation.
[0031] The intercalated multilayer Ti3C2T x MXene materials were dispersed with water and ultrasonically assisted to separate, and then filtered through filter paper to obtain a single layer of Ti3C2T x MXene flakes. Single-layer Ti3C2T x The MXene flakes were heated to 60 °C in a vacuum oven for 12 h to remove moisture and residual substances.
[0032] 30 mL of 1 mg / mL monolayer Ti3C2T x MXene flakes and urea were mixed in a mass ratio of 1:60 and stirred evenly with the assistance of ultrasound. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed. The autoclave was placed in a constant temperature box at 180°C and heated for 8 hours to carry out a solvothermal reaction.
[0033] The product after the solvothermal reaction was washed with ethanol and dried in vacuum to obtain nitrogen-doped Ti3C2T with high nitrogen content. x MXene / TiO2 materials.
[0034] The prepared nitrogen-doped Ti3C2T3 with high nitrogen content was characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). x The structure and properties of MXene / TiO2 materials were analyzed.
[0035] XRD results show that after etching away the Al atomic layer, the MAX phase ceramics transform into the MXene phase, and with the progress of intercalation and solvothermal reaction, the peak position of the MXene phase shifts and broadens significantly. At the same time, the standard peak of TiO2 can be seen, indicating the generation of in situ TiO2, the MXene lattice spacing increases, and an ordered stacking structure is formed.
[0036] FTIR results show that after etching away the Al atomic layer, the FTIR results show that after etching away the Al atomic layer, the FTIR results show that after etching away the Al atomic layer, the FTIR -1 The vibration absorption peaks of Ti-O and Ti-OH appeared in the range of 1400-1600cm, indicating the presence of oxides and hydroxyls on the surface of MXene. After intercalation and delamination, these peaks weakened or disappeared, while the peaks at 1400-1600cm -1 NH appeared in the range 4+ The symmetric and asymmetric stretching vibration absorption peaks indicate that the ammonium ions are successfully inserted into the MXene lattice. + The peak at 1000-1200cm -1 The vibration absorption peaks of CN and NH appeared in the range, indicating that nitrogen atoms were successfully doped on the MXene surface.
[0037] SEM results show that after etching away the Al atomic layer, the multilayer Ti3C2T x MXene materials exhibit a flake-like structure, and as intercalation and solvothermal reactions proceed, the flake-like structure becomes thinner, flatter, and smoother.
[0038] XPS results show that as intercalation and solvothermal reactions proceed, the high-resolution N1s spectrum can determine the presence of three different types of nitrogen in nitrogen-doped MXene / TiO2: substitutional (N-Ti), bridging (NC-Ti), and pyridinic (NCC).
[0039] The above characterization methods confirm that the high nitrogen content nitrogen-doped Ti3C2Nx MXene material prepared in this example has good structure and performance.
[0040] In order to evaluate the application performance of the high nitrogen content nitrogen-doped MXene / TiO2 material prepared in this example, it was tested for electrochemical capacitors.
[0041] In terms of electrochemical capacitors, high nitrogen content nitrogen-doped MXene / TiO2 materials were dissolved in a small amount of deionized water to make a uniform dispersion. After the dispersion was vacuum filtered, it was heated to 60°C in a vacuum box for 12 hours to prepare high nitrogen content nitrogen-doped MXene / TiO2 composite flexible thin film electrodes. The composite electrode was assembled into a symmetrical supercapacitor with polyacrylamide (PAA) gel as a diaphragm and 1M H2SO4 solution as an electrolyte, and the performance was tested on an electrochemical workstation. The results showed that the high nitrogen content nitrogen-doped MXene / TiO2 composite flexible electrode had excellent specific capacitance and cycle stability. At a current density of 1A / g, its specific capacity reached 480F / g, and after 5000 cycles, it still maintained more than 84% of the initial specific capacitance. This shows that high nitrogen content nitrogen-doped MXene / TiO2 materials have good application prospects.
[0042] [Example 2]
[0043] This embodiment provides a method for preparing nitrogen-doped Ti3C2T3 with high nitrogen content. x The method of MXene / TiO2 material, the specific steps are as follows:
[0044] 3.2 g of lithium fluoride was dissolved in HCI (9M, 30 mL) in a polytetrafluoroethylene beaker, Ti3AlC2 MAX phase powder (2 g) was slowly added, the mixture was heated to 40 ° C, stirred in a sealed beaker for 48 hours, and then the mixture was diluted 50 times with water and centrifuged at 3500 rpm for 1 min. The centrifugal washing was repeated at least 5 times until the supernatant reached a pH of more than 6. The aqueous dispersion obtained at this stage contained multilayer MXene nanosheets, which were frozen in liquid nitrogen and dried in a freeze dryer for 48 hours. Multilayer MXene powder was obtained.
[0045] Multilayer Ti3C2T x The MXene material was washed with deionized water to a pH of 7, then washed with ethanol and dried in vacuum. x The MXene material was added to 0.5-1 M ammonium chloride and stirred thoroughly for 4 h for intercalation.
[0046] The intercalated multilayer Ti3C2T x MXene materials were dispersed with water and ultrasonically assisted to separate, and then filtered through filter paper to obtain a single layer of Ti3C2T x MXene flakes. Single-layer Ti3C2T x The MXene flakes were heated to 60 °C in a vacuum oven for 12 h to remove moisture and residual substances.
[0047] 30 mL of 1 mg / mL monolayer Ti3C2T x MXene flakes and urea were mixed in a mass ratio of 1:50 and stirred thoroughly with the assistance of ultrasound. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed. The autoclave was placed in a constant temperature box at 150°C and heated for 8 hours to carry out a solvothermal reaction.
[0048] The product after the solvothermal reaction was washed with ethanol and dried in vacuum to obtain nitrogen-doped Ti3C2T with high nitrogen content. x MXene / TiO2 materials.
[0049] [Example 3]
[0050] This embodiment provides a method for preparing nitrogen-doped Ti3C2T3 with high nitrogen content. x The method of MXene / TiO2 material, the specific steps are as follows:
[0051] 3.2 g of lithium fluoride was dissolved in HCI (9M, 30 mL) in a polytetrafluoroethylene beaker, Ti3AlC2 MAX phase powder (2 g) was slowly added, the mixture was heated to 40 ° C, stirred in a sealed beaker for 48 h, and then the mixture was diluted 50 times with water, and then centrifuged at 3500 rpm for 1 min, and the centrifugal washing was repeated at least 5 times until the supernatant reached a pH of more than 6. The aqueous dispersion obtained at this stage contained multilayer MXene nanosheets, which were frozen in liquid nitrogen and dried in a freeze dryer for 48 h to obtain multilayer MXene powder.
[0052] Multilayer Ti3C2T x The MXene material was washed with deionized water to a pH of 7, then washed with ethanol and dried in vacuum. x The MXene material was added into 0.5-1 M ammonia water and stirred thoroughly for 4 h for intercalation.
[0053] The intercalated multilayer Ti3C2T x MXene materials were dispersed with water and ultrasonically assisted to separate, and then filtered through filter paper to obtain a single layer of Ti3C2T x MXene flakes, a single layer of Ti3C2T x The MXene flakes were heated to 60 °C in a vacuum oven for 12 h to remove moisture and residual substances.
[0054] 30 mL of 1 mg / mL monolayer Ti3C2T xMXene flakes and urea were mixed in a mass ratio of 1:40 and stirred thoroughly with the assistance of ultrasound. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed. The autoclave was placed in a constant temperature box at 150°C and heated for 5 hours to carry out a solvothermal reaction.
[0055] The product after the solvothermal reaction was washed with ethanol and dried in vacuum to obtain nitrogen-doped Ti3C2T with high nitrogen content. x MXene / TiO2 materials.
[0056] [Example 4]
[0057] This embodiment provides a method for preparing nitrogen-doped Ti3C2T3 with high nitrogen content. x The method of MXene / TiO2 material, the specific steps are as follows:
[0058] 3.2 g of lithium fluoride was dissolved in HCI (9M, 30 mL) in a polytetrafluoroethylene beaker. Ti3AlC2 MAX phase powder (2 g) was slowly added. The mixture was heated to 40 ° C and stirred in a sealed beaker for 48 h, then the mixture was diluted 50 times with water and centrifuged at 3500 rpm for 1 min. The centrifugal washing was repeated at least 5 times until the supernatant reached a pH of more than 6. The aqueous dispersion obtained at this stage contained multilayer MXene nanosheets, which were frozen in liquid nitrogen and dried in a freeze dryer for 48 h to obtain multilayer MXene powder.
[0059] Multilayer Ti3C2T x The MXene material was washed with deionized water to a pH of 7, then washed with ethanol and dried in vacuum. x The MXene material was added to 0.5-1 M ethylenediamine and stirred thoroughly for 4 h for intercalation.
[0060] The intercalated multilayer Ti3C2T x MXene materials were dispersed with water and ultrasonically assisted to separate, and then filtered through filter paper to obtain a single layer of Ti3C2T x MXene flakes. Single-layer Ti3C2T x The MXene flakes were heated to 60 °C in a vacuum oven for 12 n to remove moisture and residual substances.
[0061] 30 mL of 1 mg / mL monolayer Ti3C2T x MXene flakes and urea were mixed in a mass ratio of 1:50 and stirred thoroughly with the assistance of ultrasound. The mixture was transferred to a polytetrafluoroethylene-lined autoclave and sealed. The autoclave was placed in a constant temperature box at 150°C and heated for 12 hours to carry out a solvothermal reaction.
[0062] The product after the solvothermal reaction was washed with ethanol and dried in vacuum to obtain nitrogen-doped Ti3C2T with high nitrogen content. x MXene / TiO2 materials.
Claims
1. A method for preparing nitrogen-doped MXene materials with high nitrogen content, characterized in that: The following steps are involved: 1) The MAX phase ceramic material is etched to remove the A atomic layer to obtain a multilayer MXene material; 2) Intercalating and layering multilayer MXene with compounds that can ionize ammonium ions; 3) Using nitrogen-containing compounds as nitrogen sources to carry out solvothermal reaction with single-layer MXene.
2. The method according to claim 1, characterized in that The step of etching away the A atomic layer is carried out using an acidic solution plus a fluoride salt. The acidic solution is hydrochloric acid, sulfuric acid, nitric acid, oxalic acid or citric acid. The fluoride salt is lithium fluoride, ammonium fluoride, calcium fluoride, sodium fluoride or sodium hydrofluoride.
3. The method according to claim 1, characterized in that: The compound capable of ionizing ammonium ions is ammonium citrate, thioacetamide, urea, glycine, and the like.
4. The method according to any one of claims 1 to 4, characterized in that After etching, the multilayer MXene is washed to a pH > 6 to remove residual substances such as etchants.
5. The method according to any one of claims 1 to 5, characterized in that: The multilayer MXenes were ultrasonically treated after intercalation and delamination to obtain monolayer or few-layer MXenes.
6. The method according to any one of claims 1 to 6, characterized in that The multilayer MXenes were washed after intercalation to remove impurities.
7. The method according to any one of claims 1 to 5, characterized in that: In the solvothermal reaction, urea, ethylenediamine, triethylamine, tetraethylamine, etc. are used as nitrogen-containing compounds, the reaction mass ratio of the few-layer MXene material to the nitrogen source is 1:10~50, and water, glycerol, etc. are used as solvents.
8. The method according to claim 7, characterized in that The solvent heat treatment process conditions are: 120-250° C., heat preservation for 5-20 hours.
9. Application of the nitrogen-doped MXene / TiO2 material prepared by the method of claim 1 in electrochemical energy storage, comprising: Supercapacitors, lithium-ion batteries, etc.
Citation Information
Cited By
Nitrogen-doped MXenes aerogel as well as preparation method and application thereof
CN120646833A